Influence of suspension characteristics on the morphology of 3Y-ZrO2 granules produced by a spray drying process - Kunjana Suwunnasung (2018)
A systematic study was performed to determine how the 3Y-ZrO2 formulation (e.g. pH, dispersant level, binder addition) affects the granule characteristics. Suspensions consisting of 50 wt.% of 3Y-ZrO2 particles, 0.25 wt.% polyacrylic acid (PAA) as a dispersant and 1.5 wt.% polyvinyl alcohol as a binder were investigated using settling experiments and rheological analyses. Strong correlation exists between zeta potential, particle size volume, yield stress and viscosity. The isoelectric point (IEP) of 3Y-ZrO2 suspension occurred at pH 6. Adsorption of the polyelectrolyte (PAA) on the particle surface moved the IEP to lower pH and increased the negative zeta potential in a large range of pH above the IEP. A minimum of 0.25 wt% PAA moved the IEP from pH 6 down to lower pH values around 3. At pH 4, flocculated suspension leads to the formation of solid granules whereas a dispersed suspension at pH 10 leads to hollow granules.